Higher order Hilbert-Schmidt Hankel forms and tensors of analytical kernels - Ferguson, Sarah H.; Rochberg, Richard (Mathematica Scandinavica, 2005)
The symbols of $n^{\hbox{th}}$-order Hankel forms defined on the product of certain reproducing kernel Hilbert spaces $H(k_{i})$, $i=1,2$, in the Hilbert-Schmidt class are shown to coincide with the orthogonal complement in $H(k_{1})\otimes H(k_{2})$ of the ideal of polynomials which vanish up to order $n$ along the diagonal. For tensor products of weighted Bergman and Dirichlet type spaces (including the Hardy space) we introduce a higher order restriction map which allows us to identify the relative quotient of the $n^{\hbox{th}}$-order ideal modulo the $(n+1)^{\hbox{st}}$-order one as a direct sum of single variable Bergman and Dirichlet-type spaces. This generalizes the well understood $0^{\hbox{th}}$-order case.